KORELASI KETERAMPILAN MEMBACA TEKS LAPORAN HASIL OBSERVASI DAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 21 PADANG - Martin, Savira Efyana; Emidar, Emidar (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study consists of three things. First, to describe the skills to read the report text of the observation results of class VII students at SMP Negeri 21 Padang. Second, to describe the writing skills of report observation texts of class VII students of SMP Negeri 21 Padang. Third, to describe the correlation between the skills to read the text of the observation report and the text writing skills of the observation results of the seventh grade students at SMP Negeri 21 Padang.This type of research is quantitative with descriptive method. The design of this study is correlational. The population of this study was seventh grade students of SMP Negeri 21 Padang who were enrolled in the 2018/2019 school year as many as 219 people and spread in seven classes. The sample of this study amounted to 42 people who were determined using proportional random sampling technique. The research data was obtained through two types of tests, namely objective tests and performance tests. Objective tests are used to collect data on the skills to read the text of the observation report while the performance test is used to collect data on the skills to write the text of the observation report.Â Kata kunci: Korelasi, Keterampilan Membaca, Teks Laporan Hasil Observasi